Fuzzy behavior-based control of mobile robots. - Vadakkepat, P.
An extensive fuzzy behavior-based architecture is proposed for the control of mobile robots in a multiagent environment. The behavior-based architecture decomposes the complex multirobotic system into smaller modules of roles, behaviors and actions. Fuzzy logic is used to implement individual behaviors, to coordinate the various behaviors, to select roles for each robot and, for robot perception, decision-making, and speed control. The architecture is implemented on a team of three soccer robots performing different roles interchangeably. The robot behaviors and roles are designed to be complementary to each other, so that a coherent team of robots exhibiting good collective behavior is obtained.
Keywords: Decision making; Fuzzy behavior-based control; Fuzzy logic; Mobile robots; Multiagent environment; Robot perception; Soccer robots; Speed control